Knowledge and awareness of long-term and late treatment consequences amongst colorectal cancer survivors: A qualitative study. (February 2016) - Brown, Sarah; Greenfield, Diana; Thompson, Joanne
Abstract: Purpose: To describe patient knowledge and awareness of long-term and late onset treatment consequences amongst colorectal cancer survivors. Methods: Semi-structured qualitative interviews were conducted with 19 colorectal cancer survivors at least 12 months post-treatment. Interviews were audio-recorded, transcribed into NVivo 10 software and analysed using the framework method. Results: Participants were aware of disease recurrence but not many other treatment consequences; change in bowel habit and impact on diet were common and had significant impact, yet many felt they had not received 'warning', considering it a gap in both information and support. Participants expressed preference to know about possible consequences early on and were willing to engage in education and support if offered. Information overload, timing of information provision and unequipped health care professionals were considered barriers to awareness. Conclusion: Improvement in information provision, management of expectations and support around bowel function would facilitate patient self-empowerment and could improve holistic management of health and well-being after cancer. Highlights: Colorectal cancer survivors were interviewed about long-term treatment consequences. Survivors were aware of disease recurrence, but few treatment consequences. Awareness varies between individuals and is underpinned by personal experience. Change in bowel habit & diet after treatment were the most significant consequences. Participants expressed preference to be educated about treatment consequences early.